การจำลองและการสร้างภาพนามธรรมของผลกระทบการขาดแคลนน้ำต่อการเติบโตของถั่วเหลือง - อนุชิต จิตพัฒนกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The plant growth at each time step can be described by a mathematical model. In recent years, a logistic growth model has been used to simulate plant growth by ignoring water famine factor. This thesis proposed a plant growth model which depends on water famine factor. The study focuses on soybean. The resulting model can be used to simulate soybean growth based on water famine factor. Another resulting model can be used to control the growth of virtual soybean generated by the Bracketed L-system.